Здоровье вашей собаки - Баранов Анатолий Евгеньевич (НПО РИМЭКС, 1993)
Экземпляры: С/а ДБ (20140718) / Инвентарный номер: 101258 / Цена: 10.00 / Сис.шифр: 46.73 / Авт.знак: Б 24 / ГРНТИ: 68.39 / ББК: 46.7